Spatio-Temporal Variation in the Prevalence of Major Mastitis Pathogens Isolated From Bovine Milk Samples Between 2008 and 2017 in Ontario, Canada - Acharya, Kamal Raj; Brankston, Gabrielle; Slavic, Durda; Greer, Amy L. (Frontiers in Veterinary Science, 2021)
An understanding of the spatio-temporal distribution of several groups of mastitis pathogens can help to inform programs for the successful control and management of mastitis. However, in the absence of an active surveillance program, such information is not readily available. In this retrospective study, we analyzed passive surveillance data from a diagnostic laboratory with an aim to describe the spatio-temporal trend of major mastitis pathogens between 2008 and 2017 in Ontario dairy cattle. Data for all milk culture samples submitted to the Animal Health Laboratory at the University of Guelph between 2008 and 2017 was accessed. Descriptive analyses were conducted to identify the major pathogens and Chi-square goodness-of-fit tests were used to compare between multiple proportions. Likewise, univariable logistic regression analysis was performed to determine if there was a change in the probability of isolating the major mastitis pathogens depending on geography or time. Seasonality was assessed by calculating the seasonal relative risk. Of a total of 85,979 milk samples examined, 61.07% of the samples showed no growth, and the proportion of samples that showed no growth almost halved during the study period. Of the samples (36.21%, n=31,133) that showed any growth, the major bacterial pathogens were Staphylococcus aureus (15.60%), Non-aureus Staphylococci (5.04%), Corynebacterium spp. (2.96%), and Escherichia coli (2.00%). Of the Non-aureus Staphylococci, the major species reported were Staphylococcus chromogenes (69.02 %), Staphylococcus simulans (14.45%), Staphylococcus epidermidis (12.99 %), and Staphylococcus hyicus (2.13 %). A temporal change in the prevalence of contagious pathogens like Staphylococcus aureus and Corynebacterium spp. was observed with an increasing odds of 1.06 and 1.62 respectively. Likewise, except for Trueperella pyogenes, the prevalence of all the major environmental mastitis pathogens increased during the study period. The isolation of most of the pathogens peaked in summer, except for Staphylococcus aureus, Trueperella pyogenes, and Streptococcus dysgalactiae which peaked in the spring months. Interestingly, a regional pattern of isolation of some bacterial pathogens within Ontario was also observed. This study showed a marked spatio-temporal change in the prevalence of major mastitis pathogens and suggests that a regional and seasonal approach to mastitis control could be of value.